Intellectual property law - Bently, L.; Sherman, Brad. (Oxford : Oxford University Press, 2004)
This new edition has been fully revised and updated to incorporate developments in this fast-moving area of the law. It provides a comprehensive treatment of the core areas of Intellectual Property and is useful for students at undergraduate and postgraduate levels
Includes bibliographical references and index.
eng.
Keywords: Intellectual property -- Great Britain; Copyright